2023
DOI: 10.3390/vaccines11010159
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Vaccine Intention among Nurses Who Have Been Fully Vaccinated against COVID-19: Evidence from Greece

Abstract: Seasonal influenza continues to be a significant public health issue causing hundreds of thousands of deaths annually. Nurses are a priority risk group for influenza vaccination and a high vaccine uptake rate among them is crucial to protect public health. Thus, the aim of our study was to estimate the levels of influenza vaccine acceptance, as well as its determinants, among nurses for the 2022/2023 season. We conducted a cross-sectional study with a convenience sample in Greece. We collected data via an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Moreover, low levels of seasonal influenza vaccine intention among nurses in Greece for the 2022/2023 season (57.3%) are an alarmed sign of vaccine hesitancy in the country. 36 We found that COVID-19-related burnout affect negatively the intention of cardiac patients to accept a booster dose. Earlier studies in Greece confirm this finding including samples from the general population and nurses.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, low levels of seasonal influenza vaccine intention among nurses in Greece for the 2022/2023 season (57.3%) are an alarmed sign of vaccine hesitancy in the country. 36 We found that COVID-19-related burnout affect negatively the intention of cardiac patients to accept a booster dose. Earlier studies in Greece confirm this finding including samples from the general population and nurses.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, low levels of seasonal influenza vaccine intention among nurses in Greece for the 2022/2023 season (57.3%) are an alarmed sign of vaccine hesitancy in the country. 36…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 pandemic continues to evolve, individuals’ fear of the disease is decreasing and that can result in less adherence to preventive measures such as vaccination, mask wearing, hand washing, etc. Early studies among nurses showed that higher levels of exhaustion due to measures against COVID-19 reduced influenza vaccination intention [ 46 ], while increased compliance with hygiene measures was associated with increased COVID-19 booster dose hesitancy [ 47 ]. Moreover, vaccine hesitancy could be another factor that contributes to low willingness in our participants to get vaccinated against influenza.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that previous COVID-19 vaccination was negatively associated with the willingness to vaccinate against seasonal influenza due to the perceived fear of multiple COVID-19 doses and boosters taken during the pandemic [ 24 ]. Another study found that those who reported side effects from the COVID-19 vaccine were 13% less willing to take the SIV [ 25 ]. In addition, a recent study conducted in Saudi Arabia during the pandemic highlighted concerns regarding the potential interaction between SIV and the COVID-19 vaccine, in addition to concerns relating to the uptake of multiple COVID-19 boosters negatively affecting SIV uptake [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous COVID-19 vaccination was associated with a low intention to be vaccinated against seasonal influenza [ 24 ]. Low SIV uptake intention post the COVID-19 era was suggested to be due to mistrust of the healthcare system and the absence of perceived risk—as seasonal influenza is not lethal nor could it lead to severe complications or due to the fear of side effects [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%